The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1074/jbc.ac119.011170
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide CRISPR/Cas9 screen reveals that the aryl hydrocarbon receptor stimulates sphingolipid levels

Abstract: Sphingolipid biosynthesis generates lipids for membranes and signaling that are crucial for many developmental and physiological processes. In some cases, large amounts of specific sphingolipids must be synthesized for specialized physiological functions, such as during axon myelination. How sphingolipid synthesis is regulated to fulfill these physiological requirements is not known. To identify genes that positively regulate membrane sphingolipid levels, here we employed a genome-wide CRISPR/Cas9 loss-of-func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 50 publications
1
29
0
Order By: Relevance
“…Experiments to determine MAG levels in lymphocyte cultures obtained from the blood of the patients yielded very low cDNA copy numbers, so we were not able to confirm this finding in our patients. Recently, AHR was found to bind and activated the gene promoter of serine palmitoyltransferase small subunit A (SPTSSA), which encodes a subunit of the serine palmitoyltransferase that catalyzes the first and rate-limiting step in de novo sphingolipid biosynthesis (Majumder et al, 2020). Thus analysis of genes related to lipid metabolism would constitute a logical next step in our studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments to determine MAG levels in lymphocyte cultures obtained from the blood of the patients yielded very low cDNA copy numbers, so we were not able to confirm this finding in our patients. Recently, AHR was found to bind and activated the gene promoter of serine palmitoyltransferase small subunit A (SPTSSA), which encodes a subunit of the serine palmitoyltransferase that catalyzes the first and rate-limiting step in de novo sphingolipid biosynthesis (Majumder et al, 2020). Thus analysis of genes related to lipid metabolism would constitute a logical next step in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…AHR knockout mice (AHR-KO) were shown to possess an impaired optic nerve myelin sheath and exhibited modifications in lipid composition as well as in the expression of myelin-associated glycoprotein (MAG) (Juricek et al, 2017;Shackleford et al, 2018). Supporting the involvement of lipids in this pathology, AHR was recently shown to activate the promoter for a small subunit of the serine palmitoyltransferase, the first and rate-limiting step in sphingolipid synthesis, in both mice and HeLa cells (Majumder et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Recently a new mechanism regulating the expression of SPT has been described [106]. Using genome-wide CRISPR/Cas9 screening it was demonstrated that AHR (aryl hydrocarbon receptor) binds and activates the gene promoter of SPT [106].…”
Section: De Novo Synthesismentioning
confidence: 99%
“…Recently a new mechanism regulating the expression of SPT has been described [106]. Using genome-wide CRISPR/Cas9 screening it was demonstrated that AHR (aryl hydrocarbon receptor) binds and activates the gene promoter of SPT [106]. Moreover, tissues from AHR KO mice were characterized by reduced expression of several other key genes in the SL biosynthetic pathway and decreased the SL content [106].…”
Section: De Novo Synthesismentioning
confidence: 99%
See 1 more Smart Citation